Linguistic validation of the Sexual Inhibition and Sexual Excitation Scales (SIS/SES) translated into five South Asian languages: Oxford Sexual Dysfunction Study (OSDS) - Malavige, Lasantha S (BioMed Central, 2013)
BACKGROUND: The purpose of the linguistic validation of the Sexual Inhibition and Sexual Excitation Scales (SIS/SES) was to produce translated versions in five South Asian languages (Hindi, Urdu, Panjabi, Tamil and Sinhalese) that was “conceptually equivalent” to the original U.S. English version, for use in the Oxford Sexual Dysfunction Study (OSDS). METHODS: Initially an expert committee was appointed to carry out the task of linguistic validation. This committee included the principal investigator, project coordinator and the associate project manager of the OSDS and a language consultant for each of the South Asian languages. The process of translation and validation was conducted in the following order; a) production of two independent forward translations, b) comparison and reconciliation of the translations, c) backward translation of the first reconciled version, d) comparison of the original version of SIS/SES and the backward version leading to the production of the second reconciled version and e) pilot testing and finalization. RESULTS: Several linguistic and conceptual issues arose during the process of translating the instrument. Problems were also encountered with cultural differences in acceptability of certain concepts, and with semantic difficulties in finding an appropriate translation. In addition, the researchers had to find culturally acceptable equivalents for some terms and idiomatic phrases. The problems encountered in pilot testing, during cognitive debriefing and clinicians’ review, were categorized as cultural or conceptual/semantic. Cultural issues describe the acceptability of using certain terms and phrases in a particular socio-cultural milieu. The conceptual and semantic difficulties reflect the inability to deliver the idea/meaning of a source statement in the target language. The current paper describes a selection of these issues. CONCLUSIONS: We applied a rigorous translation method to ensure conceptual equivalence and acceptability of SIS/SES in the five different South Asian languages prior to its utilization in the OSDS. However, to complete the cultural adaptation process, future psychometric validation of the translated versions is required among the different language speakers.